Anchoring number-performance relationship of zinc-porphyrin sensitizers for dye-sensitized solar cells: A combined experimental and theoretical study - Tinnagon Keawin (2018)
© 2016 Elsevier Ltd Porphyrin dyes have received much attention recently, due to their excellent photovoltaic performances in dye-sensitized solar cell (DSSC) applications. In this study, a series of zinc-porphyrin sensitizers, 1PEP, 2PEP, and 3PEP were synthesized with 1, 2, or 3 anchoring groups, respectively, at meso-positions on the porphyrin ring, and their photophysical, electrochemical, and photovoltaic properties were investigated. Our results reveal that different numbers of anchoring groups significantly affect cell performance. We found that DSSC conversion efficiency decreases with increasing numbers of anchoring groups present on the porphyrin ring, and that the presence of 2 and 3 carboxyl anchors have an electron withdrawing effect on the porphyrin macrocycle. Compared to 1PEP, there is a reduction in 2PEP and 3PEP power conversion efficiency (η) values as a consequence of lower electron-injection efficiency, which is apparent from the weaker photocurrents (Jsc) exhibited by these compounds. 1 PEP, produces the greatest η value of 4.01%. We performed theoretical calculations for the dyes and dye@TiO 2 complexes to further investigate the reduction in η values that occurs with increasing numbers of anchoring groups. Calculated results reveal that 2PEP and 3PEP, bearing greater numbers of anchoring groups, suppress electron injection into the TiO 2 conduction band (CB), resulting in reduced Jsc currents and power-conversion efficiency.